Understanding Consumer Behavior Through Big Data Analytics: Evidence from the Smartphone Industry - Mohamed, Bouaddi; Mohammed, Beddaa; Siham, Khaldi (PT.KARYA GEMAH RIPAH, 2026)
In an era dominated by digital interactions, the utilization of Big Data has become essential for businesses striving to comprehend and anticipate consumer behavior. This study investigates the impact of Big Data on understanding consumer behavior and enhancing customer satisfaction within the smartphone market. A quantitative research design was employed, involving a sample of 300 smartphone users surveyed through a structured questionnaire. Utilizing Structural Equation Modeling (SEM), the analysis revealed significant positive relationships: Big Data positively influences the understanding of consumer behavior and consumer satisfaction, while a deeper understanding of consumer behavior also enhances satisfaction. The strong statistical significance of these findings underscores the strategic value of Big Data for businesses aiming to optimize customer experiences and maintain competitive advantage. Furthermore, the study highlights key recommendations for organizations looking to leverage Big Data effectively. Companies should invest in robust data analytics platforms, implement advanced analytics tools for effective customer segmentation, and utilize machine learning algorithms to anticipate consumer trends. Ethical considerations are paramount; organizations must ensure transparency in data collection and comply with privacy regulations to foster consumer trust. Future research should explore the long-term effects of Big Data utilization on consumer satisfaction and examine its applications across different industries. Overall, this study affirms that effective data analytics not only enhances consumer insights and satisfaction but also strengthens relationships between businesses and their customers in an increasingly competitive market landscape.